MOOCs Usage in Russian Higher Educational Institutions: Why Is Not There Any Increasing Demand for MOOCs During Emergency Distance Learning - U. S. Zakharova; K. A. Vilkova; R. N. Abramov (Moscow Polytechnic University, 2023)
The abrupt transition to distance learning during the outbreak of the COVID-19 pandemic triggered an urgent need for online resources at higher education institutes (HIEs). Creating analogues of traditional full-time courses demanded for competencies and time resources. In this case ready-made massive open online courses (MOOCs) were supposed to be the most obvious and fastest solution for HIEs. However, analytics demonstrated that educational institutions did not consider MOOC a promising option. This contradiction served as an incentive to conduct this research, which includes the analysis of both non-reactive (MOOCs platform analytics) and reactive (online survey and interviews with instructors) data. Based on our research, we can conclude that the reasons for not integrating MOOCs at Russian HIEs during the COVID-19 pandemic are the following: the peculiarities of MOOCs format, low motivation of instructors, administrative risks, and the uncertainty of HIEs' and national policies on MOOCs integration. This article will be useful for those who determine educational policy in Russia, university administrators, methodologists responsible for the development of digital educational technologies in HIEs, as well as researchers of higher education.